2005
DOI: 10.3189/172756505781829566
|View full text |Cite
|
Sign up to set email alerts
|

A distributed surface energy-balance model for complex topography and its application to Storglaciären, Sweden

Abstract: ABSTRACT. A grid-based surface energy-balance mass-balance model has been developed to simulate snow-and ice melt in mountainous regions with an hourly resolution. The model is applied to Storglaciären, a valley glacier in Sweden, using a 30 m resolution digital elevation model. Emphasis is directed towards computing the radiation components. These are modelled individually, considering the effects of slope angle, aspect and effective horizon. A new parameterization for snow albedo is suggested, modifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
342
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(351 citation statements)
references
References 71 publications
8
342
0
1
Order By: Relevance
“…Sensitivity analysis of the model parameters can be used to assess uncertainties in the annual mass balance. Previous work has shown that the model output is most sensitive to parameters in parameterizations of α and turbulent heat fluxes, temperature lapse rate (T rate ), precipitation lapse rate (P rate ) and air temperature thresholds for snow (T snow ) and rain (T rain ) ( Mölg and Hardy, 2004;Hock and Holmgren, 2005;others, 2008, Reijmer andHock, 2008;Zhu and others, 2015). Both T rate and P rate on MZ15 glacier were derived from field measurements, and uncertainties in the model parameters are associated with the a snow , a firn and snow (or ice) exchange coefficient of turbulent heat flux (C S ) due to a lack of direct measurements.…”
Section: Glacier Mass-balance Modelmentioning
confidence: 99%
“…Sensitivity analysis of the model parameters can be used to assess uncertainties in the annual mass balance. Previous work has shown that the model output is most sensitive to parameters in parameterizations of α and turbulent heat fluxes, temperature lapse rate (T rate ), precipitation lapse rate (P rate ) and air temperature thresholds for snow (T snow ) and rain (T rain ) ( Mölg and Hardy, 2004;Hock and Holmgren, 2005;others, 2008, Reijmer andHock, 2008;Zhu and others, 2015). Both T rate and P rate on MZ15 glacier were derived from field measurements, and uncertainties in the model parameters are associated with the a snow , a firn and snow (or ice) exchange coefficient of turbulent heat flux (C S ) due to a lack of direct measurements.…”
Section: Glacier Mass-balance Modelmentioning
confidence: 99%
“…However, COSIMA was developed independently from the existing models. Compared to other commonly used SEB and MB approaches (e.g., Hock and Holmgren, 2005;Klok and Oerlemans, 2002;Pellicciotti et al, 2009) the parameterization of subsurface energy and mass fluxes within COSIMA is more sophisticated and directly coupled to the surface processes. COSIMA explicitly calculates meltwater percolation, the refreezing process within the snowpack under consideration of latent heat release and resulting subsurface melt, as well as the effects on subsurface temperature, snow density, and ground heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…The snow line separates two glacier parts with different albedo and therefore SEB processes (Hock and Holmgren, 2005). Thus, the accurate estimation of the snow line's temporal evolution is an important factor for melt modeling, especially for the so-called "summer-accumulation type" (SAT) glaciers.…”
Section: Introductionmentioning
confidence: 99%
“…be used for modelling glacier mass balance as slope and aspect are common parameters for energy balance-type models (Hock, 2005;Hock & Holmgren, 2005). Nevertheless, much of the glacier surface is relatively smooth with a mean slope of 10°(with a minimum slope of 0.5°and a maximum of 75°).…”
Section: Other Considerationsmentioning
confidence: 99%